Methodology employed in Croatian Orthography (1944), a morphophonological orthography book - Mihaela Matešić (Rasprave Instituta za Hrvatski Jezik i Jezikoslovlje, 2014)
In Croatian Orthography (1944), created in the Office for the Croatian Language, it is stated that it was compiled by two members of the Office – Franjo Cipra and Adolf Bratoljub Klaić, with the help of the other members of the Office. This is the only Croatian orthography book based exclusively on the morphophonological orthographic principle the use of which was officially prescribed (the Decision of the Ministry of National Education, 3rd November 1943). Since this orthographic book represents a deviation from the general direction of the development of then contemporary orthographic norm, which was a predominantly phonological one (that is, phonological-morphological), the methodology used for its compilation is of particular interest. In this sense, the analysis focuses on three aspects: determination of the range of orthographic relevance (the scope of individual issues dealt with under the umbrella of orthographic topics), definitions of certain orthographic rules (the meta-language of the orthography book, that is, how popular-scientific discourse intended for communication with users is built in the book), and the structure of the orthographic book (the level of treatment of individual orthographic issues: their treatment in chapters, the dictionary section, appendices, etc.). Besides analysing the methodology employed for the compilation of this orthography – a book that, curiously, has no introduction or an afterword – the paper also analyses its relations with other Croatian orthography books.